2019
DOI: 10.1186/s12871-019-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volume-controlled ventilation mode and pressure-controlled ventilation with volume-guaranteed mode in the prone position during lumbar spine surgery

Abstract: Background During lumbar spine surgery, patients are placed in the prone position for surgical access. The prone position has various effects on cardiac and pulmonary function, including a decreased cardiac index (CI), decreased dynamic lung compliance (Cdyn), and increased peak inspiratory pressure (Ppeak). In this study, we compared the volume-controlled ventilation mode (VCV) and pressure-controlled ventilation with volume guaranteed mode (PCV-VG) based on hemodynamic and pulmonary variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Another agreement with our study, Lee et al, showed that arterial blood gas results did not differ significantly between the two groups receiving (PCV-VG and VCV) when comparing 36 patients undergoing lumbar spine surgery in the prone position (Lee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another agreement with our study, Lee et al, showed that arterial blood gas results did not differ significantly between the two groups receiving (PCV-VG and VCV) when comparing 36 patients undergoing lumbar spine surgery in the prone position (Lee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Of those, 351 had to be excluded, resulting in 21 publications that were full-text assessed for eligibility. Four publications had to be excluded, finally resulting in 17 studies that underwent the following qualitative evaluation [ 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A flow chart of the search strategy and study selection are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This increases power consumption by the myocardium, while his ability to do this can be in varying degrees limited. It is known that SA, performed using the same technique and reaching the same level, does not lead to circulatory disorders in some patients, while in others it causes severe destabilization [4]. The only reasonable explanation for this fact, from our point of view, is that the autoregulation of CS in different individuals is carried out with the predominance of different mechanisms, which, however, provide an adequate supply of energy to tissues under average daily loads.…”
Section: Rs Globalmentioning
confidence: 88%